The Stiletto Flies (Diptera: Therevidae) of British Columbia, Yukon, and Alaska - Gibson, Joel F.; Cannings, Robert A. (Zootaxa, 2025)
Therevidae (Stiletto Flies) is a cosmopolitan family of flies in the superfamily Asiloidea, containing over 1250 described species. There is no previously published treatment of the family in British Columbia, Yukon, and Alaska. An updated checklist of 34 species known in this region is presented based on over 2100 specimens, database records, photographs, and published records. A key based on non-genitalic characters provides identification to genera and to species where only one species of a genus is known in the region. Geographical distribution for species in each jurisdiction is given and is summarized using an ecoprovince approach for each of the 31 species in British Columbia, a comparable ecozone treatment for the 15 species known in the Yukon, and a generalized ecoregion system for the six species reported from Alaska. Where available, conservation ranks for each species are included. Ecological and behavioural information for each species, including known flight period in the region, is presented. Acrosathe vialis (Osten Sacken) is recorded new to Canada and British Columbia and Pallicephala quebecensis Webb and Irwin is reported from the Yukon for the first time.